A prospective study on the feasibility of cochlear implantation during the coronavirus disease 2019 crisis and trends of assessment: experience in a UK centre. Issue 1 (13th January 2021) - Mohammed, H; Kennedy, L; Whitehead, D; Ahmad, N; Banerjee, A
Abstract: Objectives: To demonstrate the feasibility of continuing cochlear implantation during the coronavirus disease 2019 crisis and to report on trends of referrals via the neonatal hearing screening programme. Methods: A prospective case series was conducted on children who underwent cochlear implantation during the coronavirus disease 2019 crisis in the UK and a sample of referrals via the neonatal hearing screening programme. A step-by-step description of peri-operative management is included. Results: Regionally, between February and May 2020, 106 babies were referred via the neonatal hearing screening programme to paediatric audiology. Eleven children were operated on during the coronavirus disease 2019 study period. None of the 11 children developed coronavirus symptoms. Discussion: It is widely recognised that the demands of managing the current pandemic may compromise screening, clinical assessment and elective surgery. Time-sensitive issues such as cancer management have gained prominence, but a similar need exists for timely paediatric cochlear implantation. Conclusion: Implantation in the paediatric population during the coronavirus disease 2019 pandemic is feasible with careful planning.